A novel approach to safe redo-sternotomy in a patient with aortocutaneous fistula from an infected ascending aorta graft. (July 2014) - Al-Atassi, T; Kimmaliardjuk, DM; Labinaz, M; Dickie, S; Rubens, F
This case describes a novel approach to a safe redo-sternotomy in a patient presenting with an aortocutaneous fistula from a previous infected ascending aorta graft.